Managing the margins gender, citizenship, and the international regulation of precarious employment - Vosko, Leah F. (Oxford : Oxford University Press, 2010)
Using examples from Canada, the US, Australia and the EU, this work probes national and international regulatory responses to the shift from full-time permanent jobs towards part-time temporary and self-employment. It analyzes their implications for workers most often precariously employed, particularly women and migrants.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Part-time employment; Temporary employment; Part-time employment -- Law and legislation; Temporary employment -- Law and legislation; Women -- Employment; Foreign workers; Women -- Employment -- Law and legislation; Foreign workers -- Legal status, laws, etc